The settler colonial present - Veracini, Lorenzo (Palgrave Macmillan, 2015)
Settler colonial studies emerged in the last two decades as a subfield of comparative scholarly research. The Settler Colonial Present explores the ways in which settler colonialism as a mode of domination survived the age of decolonisation and reflects on the ways in which settler colonial studies can help making sense of the current dispensation. Rather than a thing of the past, or something affecting remote semi-peripheries, settler colonialism emerges as a crucial feature of the global present.